Evaluation of the STTNF 360° Virtual Tour System Success based on the Delone and McLean Model using the PLS-SEM Approach - Syifa Rahmatia Ramadhani; Jemiro Kasih (Sistemasi: Jurnal Sistem Informasi, 2026)
This study aims to evaluate the success of the STTNF 360° Virtual Tour System as an information and promotional medium for Sekolah Tinggi Teknologi Terpadu Nurul Fikri (STTNF). The system enables prospective users to explore the campus environment virtually; however, its success from the users' perspective has not yet been systematically evaluated. This study adopts a quantitative approach based on the DeLone and McLean Information Systems Success Model to examine the effects of System Quality, Information Quality, and Service Quality on Use, User Satisfaction, and Net Benefits. Data were collected through a questionnaire administered to 97 respondents and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results indicate that System Quality has a significant positive effect on User Satisfaction (t = 2.454, p = 0.014). Furthermore, User Satisfaction has significant positive effects on both Use (t = 4.011, p < 0.001) and Net Benefits (t = 10.129, p < 0.001), whereas the remaining quality constructs do not exhibit statistically significant effects. The coefficient of determination (R²) indicates moderate explanatory power, with values of 0.527 for User Satisfaction, 0.663 for Use, and 0.511 for Net Benefits. Overall, the findings demonstrate that the STTNF 360° Virtual Tour System provides meaningful benefits by enabling users to better understand the campus environment through an immersive virtual experience. These results offer practical insights for STTNF to further improve system quality and optimize the virtual tour as an effective platform for campus information dissemination and promotion.